2010
DOI: 10.1016/j.geoderma.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of matric suction on the compressive properties of two agricultural soils using an osmotic oedometer

Abstract: The compaction of cultivated soils by agricultural machines considerably affects both the structure and physical properties of soil, thus having a major impact on crop production and the environment. Soil mechanical resistance is highly variable both in time and space because it depends on soil texture, soil porosity and soil water state (matric suction). This paper is devoted to the effect of soil matric suction on the compression index C c , which is one of the mechanical parameters that describes the soil m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
(82 reference statements)
1
6
0
8
Order By: Relevance
“…CEC characteristics of the studied soils parameters of the soil is not surprising. Some previous research results have shown that water retention is a complex function of soil structure and composition (Cui et al, 2010;Rawls et al, 2003). We observed in this study that the interaction between moisture retention and the clay content of the sample varied at different matric potential.…”
Section: Resultsmentioning
confidence: 47%
“…CEC characteristics of the studied soils parameters of the soil is not surprising. Some previous research results have shown that water retention is a complex function of soil structure and composition (Cui et al, 2010;Rawls et al, 2003). We observed in this study that the interaction between moisture retention and the clay content of the sample varied at different matric potential.…”
Section: Resultsmentioning
confidence: 47%
“…An alternative to uniaxial testing is triaxial testing, which differs in two respects: (i) both the radial and axial stresses applied to the soil are controlled and (ii) the pore water pressure is usually either controlled or measured. Although, pore water pressure can be controlled in uniaxial tests (e.g., Cui et al, 2010), it is not the norm. Triaxial testing allows the effects of both consolidation and shear deformation on soil density (or porosity) to be quantified.…”
Section: Triaxial Testing To Determine the Effect Of Soil Type And Ormentioning
confidence: 99%
“…A compactação é puramente a mudança de volume do solo (Horn et al, 2003;Keller et al, 2007), e a densidade, portanto, é uma medida física simples que efetivamente quantifica a compactação por efeito de cargas externas provenientes do tráfego (O'Sullivan et al, 1999). Entretanto, acompanhada da variação de volume, outros efeitos negativos resultados da compactação podem ser observados, tais como alterações na estrutura , sucção matricial (h) Cui et al, 2010), resistência à penetração (RP) (O'Sullivan et al, 1987;Silva et al, 1994;Keller et al, 2013) e dinâmica do fluxo de oxigênio na matriz do solo (Ball et al, 1988;Silva et al, 1994;Berisso et al, 2013).…”
Section: Dinâmica De Atributos Físicos Do Solo Pós-tráfegounclassified
“…Como colocado, mudanças de RP e h pós-tráfego trariam problemas de interpretação quanto aos danos causados para as plantas, mas são úteis como indicares de compactação e resistência do solo O'Sullivan et al, 1987;Cui et al, 2010;Severiano et al, 2013;Keller et al, 2013;Stettler et al, 2014). A RP é frequentemente usada como indicador de compactação (O'Sullivan et al, 1987;Keller et al, 2013), e h é usado nos modelos de resistência do solo (Cui et al, 2010;Severiano et al, 2013;Stettler et al, 2014). Entretanto, como a RP e h não dependem apenas da alteração de volume, alterações imediatamente pós-tráfego podem não ser observadas, mesmo com o incremento de densidade O'Sullivan et al, 1987;Cui et al, 2010).…”
Section: Dinâmica De Atributos Físicos Do Solo Pós-tráfegounclassified
See 1 more Smart Citation